A long persistent phosphorescent metal–organic framework for multi-level sensing of oxygen. Issue 29 (1st July 2020) - Zhu, Cheng-Yi; Wang, Zheng; Mo, Jun-Ting; Fan, Ya-Nan; Pan, Mei
Abstract : A novel metal–organic framework (MOF) with long persistent luminescence (LPL) for multilevel oxygen detection is proposed. Abstract : A novel metal–organic framework (MOF) with long persistent luminescence (LPL) for multilevel oxygen detection is proposed, for which, the phosphorescence intensity, phosphorescence lifetime and LPL performance were applied to detect oxygen levels in 300–100 mbar, 0–150 mbar and <8 mbar, respectively. Uniquely, the new idea of LPL detection makes the monitoring of ultra-low oxygen content possible with visualization.